Improving the Training Process for Student Providers in a Student-Run Free Clinic: Assessing the Impact of a Small Group, Peer-Led Training Process - Bailey Hassman; Lauren Hoody; William Hay (Journal of Student-Run Clinics, 2024)
Background: Student-run free clinics give students crucial opportunities to improve their skills as future medical professionals. However, many students at our institution feel unprepared to take on student provider roles despite completing a training curriculum. This study describes an improved way to train student providers using a small group, peer-led training process.Methods: Participants in the control group completed our institution’s current training process consisting of viewing e-modules and observing a clinic visit. Participants in the experimental group took part in small group, peer-led training sessions. All study participants completed pre- and post-training surveys to assess their confidence in navigating the electronic health record, performing physical exams, and patient interviewing and in their sense of overall preparedness. Participants’ pre-training to post-training confidence change scores were calculated for each question, and the two groups’ results were compared using Mann-Whitney-U tests.Results: Results revealed a statistically significant increase in confidence in performing physical exams and navigating the electronic health record for students in the experimental group compared to the control group. While both groups saw an increase in confidence in overall preparedness to serve as a student provider and in patient interviewing, no significant differences were observed between the two groups.Conclusions: While both groups showed increases in confidence change scores for all components surveyed, participants in the small group, peer-led training process reported a larger increase in their confidence to perform physical exam and electronic health record navigation skills after the training intervention than the control group participants. Small-group, peer-led training sessions give students opportunities to receive early hands-on exposure to technical skills. The findings of this study can lead to lasting improvement in our institution’s provider training process while serving as a model for other student-run clinic programs to better prepare student providers to care for at-risk populations.